Caracterização estrutural e térmica de cristais de L-Arginina•HClxHBr1-x - PEREIRA, Adriano Bezerra (2016)
Materials consisting of amino acids are of great interest in the application in nonlinear optical (NLO) and are being studied more carefully because they have properties better than the potassium dihydrogen phosphate (KDP), the material most commonly used for Second Generation Harmonic (SHG). In this work, the crystals of L-arginine hydrobromidric monohydrate (LAHBr) and L-arginine hydrochloridric monohydrate (LAHCl) were grown at room temperature (25° C) by the method of slow evaporation of solvent. Were also synthesized hydrochlorobromidric L-arginine monohydrate crystals (LAHClBr) from the mixture of the compounds in equimolar proportions 1:3, 1:1 and 3:1. These five crystals were characterized by the techniques of X-Ray Fluorescence (XRF), Diffraction X-Ray (XRD), Raman Spectroscopy, Thermogravimetry (TG), Differential Thermal Analysis (DTA) and Differential Scanning Calorimetry (DSC). The chemical composition of the single crystal was analyzed by X-ray Fluorescence (XRF) and compositions obtained were: C6H14N4O2•HCL0.14BR0.86•H2O (LAHCl0,14Br0,86), C6H14N4 O2•HCL0.42BR0.58•H2O (LAHCl0,42Br0,58), e C6H14N4O2•HCL0.63BR0.37•H2O (LAHCl0,63Br0,37). The structural parameters of the crystals were characterized by X-ray diffraction (XRD) in association with the Rietveld refinement. The all samples crystallize with the monoclinic structure (space group P21) and the unit cell volume of LAHClxBr1-x series decreases with increasing concentration of chlorine in the composition of the samples. The vibrational modes were observed by Raman Spectroscopy. The Raman spectrum experiments have shown that bands associated with lattice modes undergo blue shifts as the concentration of chorine ion is increased in addition to complement the results obtained by XRD technique. The thermal analysis of TG, DTA and DSC showed that the crystals analyzed show a decrease in temperature of the characteristic exothermic phase transition event, as well as increasing in the melting temperature of the material, with increasing chlorine concentration. The crystals LAHBr, LAHClBr and LAHCl to lose water of hydration suffer phase transformation goes to anhydrous phase without change in structure (monoclinic-monoclinic) and present structural phase transition around 150 oC.